2020
DOI: 10.1186/s12985-019-1274-x
|View full text |Cite
|
Sign up to set email alerts
|

Decay of infectious adenovirus and coliphages in freshwater habitats is differentially affected by ambient sunlight and the presence of indigenous protozoa communities

Abstract: BackgroundSanitary quality of recreational waters worldwide is assessed using fecal indicator bacteria (FIB), such as Escherichia coli and enterococci. However, fate and transport characteristics of FIB in aquatic habitats can differ from those of viral pathogens which have been identified as main etiologic agents of recreational waterborne illness. Coliphages (bacteriophages infecting E. coli) are an attractive alternative to FIB because of their many morphological and structural similarities to viral pathoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
133
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 129 publications
(142 citation statements)
references
References 93 publications
9
133
0
Order By: Relevance
“…The porous nature of the cotton fabric, increasing the surface area onto which the inoculum droplet was adsorbed and subsequently subjected to drying, is likely to augmented viral degradation thereby decreasing virus viability as well as quantification of RNA. While this manuscript was in its revision stage, a study released by Riddell and colleagues corroborated our observations on the reduced viability of SARS-CoV-2 on cotton compared to other materials 23 . Using a similarly high titer inoculum, a significant loss of infectious virus was noted after an hour of drying, though persistence was detectable up to 7 days.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…The porous nature of the cotton fabric, increasing the surface area onto which the inoculum droplet was adsorbed and subsequently subjected to drying, is likely to augmented viral degradation thereby decreasing virus viability as well as quantification of RNA. While this manuscript was in its revision stage, a study released by Riddell and colleagues corroborated our observations on the reduced viability of SARS-CoV-2 on cotton compared to other materials 23 . Using a similarly high titer inoculum, a significant loss of infectious virus was noted after an hour of drying, though persistence was detectable up to 7 days.…”
Section: Discussionsupporting
confidence: 75%
“…These discrepancies are likely due to a combination of different ambient conditions, inoculum titres, and readout assay sensitivity. Indeed, in the recently published work of Riddell and colleagues 23 , extended persistence of SARS-CoV-2 for up to 28 days was observed under experimental conditions most closely resembling those utilized herein.…”
Section: Discussionsupporting
confidence: 75%
“…Some controlled, laboratory feeding studies demonstrated uptake of various bacteriophages ( Pinheiro et al, 2007 ; Deng et al, 2014 ) and adenoviruss by predatory protozoa ( Scheid and Schwarzenberger, 2012 ). Others have observed more rapid decay of bacteriophages ( Wanjugi et al, 2016 ; Booncharoen et al, 2018 ), adenoviruses ( Rigotto et al, 2001 ; McMinn et al, 2020 ), poliovirus ( Rachmadi et al, 2016 ) and echovirus 11 ( Olive et al, 2020 ) when seeded in unprocessed water than in filtered and/or autoclaved ambient water, suggesting that microbial communities may influence viral decay rates. Compared to temperature, even less is known about the effect of protozoan predation on enveloped viruses such as SARS-CoV-2.…”
Section: Introductionmentioning
confidence: 99%
“…In-silico docking studies by our group identified various phyto-compounds that can potentially reduce SARS-CoV-2 infection at multiple stages during the course of an infection, including Withanone and Tinocordiside. 39 Tinocordiside from Tinospora cordifolia reduced the free binding energy of the host cell ACE-2 and the SARS-CoV-2 spike protein’s Receptor Binding Domain. 40 Other studies identified the potential use of several phyto-compounds such as diterpene, tetranortriterpenoid, phytosterols, and several other FDA approved compounds for efficient blocking of the major protease, Nsp9 replicase, and spike proteins of the SARS-CoV-2 virus.…”
Section: Discussionmentioning
confidence: 99%
“… 41 , 42 The various bioactive compounds present in Withania somnifera (Ashwagandha), such as Withanone, Withanoside X, Ashwagandanolide, Dihydrowithaferin A, and Withanolide N were identified as potent inhibitors to the entry of the virus into the host cell using docking experiments in-silico. 39 , 43 Others have shown the stable binding of Withanoside V to the M pro protease through dynamic simulations. 44 …”
Section: Discussionmentioning
confidence: 99%